Evaluasi Kualitas Product Operation Pada Aspek Correctness, Reliability, Effiency, Integrity Dan Usability Untuk Website Lembaga Pendidikan (Studi Pada Website Fakultas Ilmu Komputer Universitas Brawijaya) - Tria Palupi Anggraini; Admaja Dwi Herlambang; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Website filkom.ub.ac.id is a facility provided by the Faculty of Computer Science Universitas Brawijaya as a medium for disseminating important information related to academic and non academic information and to fulfill the assessment on the form so that the quality of the website must be considered for the accuracy and completeness of the published data information as well as for know the ease of operation of website for user. To be able to know the quality of website, then conducted a research in the form of evaluation of website quality Faculty of Computer Science Universitas Brawijaya use product operation concept with correctness, reliability, effiency, integrity, and usability aspects. The design of this study using descriptive and techniques used to collect data is a questionnaire with the number 98 respondents. In the descriptive analysis, the average result of the correctness variable is 82,98% with good category, the reliability variable equal to 81,05% with good category, effiency variable equal to 73,00% with good category, integrity variable equal to 82,63% with category good, and usability variable equal to 83,57% with good category in indicator communicativenes and operability, where as on training indicator at task T2, T3, and T4 have 100% effectiveness and 100% efficiency while for effectiveness T1 get score 95% and efficiency 84%. From the average of T1, T2, T3, and T4 obtained very good category for effectiveness and very good category for efficiency. Keywords: product operation, correctness, reliability, effiency, integrity, usability